2019
DOI: 10.21203/rs.2.13639/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smart Pumps Improve Medication Safety but Increase Alert Burden in Neonatal Care

Abstract: Background: Smart pumps have been widely adopted but there is limited evidence to understand and support their use in pediatric populations. Our objective was to assess whether smart pumps are effective at reducing medication errors in the neonatal population and determine whether they are a source of alert burden and alert fatigue in an intensive care environment. Methods: Using smart pump records, over 370,000 infusion starts for continuously infused medications used in neonates and infants hospitalized in a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One study reported a high volume of alerts clustered around specific patients and mediations in a NICU. 52 This can potentially lead to a high alert burden and limit DERS safety benefit by desensitizing nurses to these alerts. Another study found that due to line occlusions, drug incompatibilities, and patient factors, alarms from infusion pumps were frequent in the NICU/pediatric ICU.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a high volume of alerts clustered around specific patients and mediations in a NICU. 52 This can potentially lead to a high alert burden and limit DERS safety benefit by desensitizing nurses to these alerts. Another study found that due to line occlusions, drug incompatibilities, and patient factors, alarms from infusion pumps were frequent in the NICU/pediatric ICU.…”
Section: Discussionmentioning
confidence: 99%
“…For these hospitals, introducing unfamiliar brand-new infusion pumps, which are introduced in recent times and not used in many hospitals, can be a risk factor regardless of the performance of the device. 15 In addition, most nurses prefer to use familiar infusion pumps to overcome the necessity to re-train and adapt to the unfamiliar interface of a novel device owing to the fear of accidents from user confusion. 16 Furthermore, many vendors recommend a dedicated IV catheter with their infusion pumps to guarantee the accuracy of infusion.…”
Section: Discussionmentioning
confidence: 99%